Asymmetries in athletic performance - Afonso, J.; Bessa, C.; Pinto, F.; Ribeiro, D.; Moura, B.; Rocha, T.; Vinicius, M.; Canário-Lemos, R.; Peixoto, R.; Clemente, F. M. (Asymmetry as a Foundational and Functional Requirement in Human Movement, 2019)
Based on the knowledge portrayed in the previous chapters, it would be surprising if asymmetries were not a factor in athletic performance. Ask a person to get ready to sprint, and that person will most likely always (and unconsciously) put the same foot forward. Ask a person to punch or kick a boxing bag as hard as possible, and their lateral preferences will tend to be very strong. These preferences are self-evident and can be easily accessed. But even in scenarios where it would be theoretically beneficial to perform actions with equal prowess on both sides, this does not occur in practice. In sports such as judo, boxing, or jiu-jitsu, most high-level competitors have well-established lateral preferences. Having two equally skilled sides would certainly prove to be a competitive advantage, and so we should ask ourselves why such symmetry is not common at the highest levels of practice, even when coaches stimulate bilateral practice in athletes starting from young ages. In elite-level basketball, players don`t attempt three-point shots in equal percentages with both hands. Indeed, despite claims that bilateral asymmetries may be detrimental to sports performance, research does not entirely support this notion, as has been shown in the review of Maloney [1].